Production of Lovastatin by Penicillium spp. Soil Microfungi - Seydametova, Emine; Jailani, Salihon; N., Zainol; Convey, Peter (IACSIT Press, 2012)
Lovastatin is an important fungal secondary metabolite inhibiting the enzyme which catalyzes a rate-limiting step in the biosynthesis of cholesterol. As microfungi of the genus Penicillium are active producers of cholesterol lowering agents (statins), studies of this genus have gained considerable momentum. In Malaysia, both agricultural soils and those of natural ecosystems are valuable sources of filamentous fungi, whose biotechnological potential in terms of lovastatin production has not been well investigated. The aim of the present study is to determine lovastatin-producing potential of Penicillium spp. microfungi isolated from soil in Pahang State (Malaysia). Fungal cultures were isolated, purified, and classified based on characters of colony morphology and microscopic features. All identified representatives of Penicillium were tested for their ability to produce lovastatin. Isolates were cultivated in submerged fermentation. High-performance liquid chromatography (HPLC) was used for detection of lovastatin. Among 54 fungal cultures examined, four Penicillium strains were confirmed to produce this statin. The isolate Penicillium sp. ESF2M was the strongest lovastatin producer, with a yield of 20 mg/l. This strain should now be subjected to a further strain improvement program to maximize the yield of this important statin.